Effect of high doses of Mepiquat chloride (pix) on Egyptian cotton productivity under North Delta conditions - Elashmouny, Amany Ahmed; Elkashlan, Mohamed Kotb; Ata Allah, Youssef Fathy (Journal of agricultural, environmental and veterinary sciences, 2019)
Two field experiments were conducted during 2017 and 2018 seasons to study the effect of high doses of mepiquat chloride at rates of 0, 1, 1.5 and 2 liter/ fed on growth, phytohormones and yield of cotton plants cv. Giza 94. The experiment was conducted in Sakha, Kafr El-Shiekh Governorate, Egypt in a randomized complete block design. In the beginning of square and after 15 days from squaring, the cotton cultivars were foliar sprayed by with different doses of pix. Short internodes of 5 to 7 cm observed in spraying of different concentration of pix, while long internodes below 10 cm developed in control. As a conclusion, the results showed that, in general spraying mepiquat chloride (pix) had a significant effect on the growth of cotton plants i.e, reduction of plant height, absolute growth rate and concentration percentage of Gibberellins in cotton plants. On the other hand, spraying cotton plants with pix using 1 liter/ fed. significantly increased crop growth rate, photosynthesis pigments, number of open bolls/ plant, seed cotton yield/ Fadden compared with control and other doses.
Keywords: Pix; spraying; cotton; growth analysis and yield